Penerapan pelayanan terpadu satu pintu dalam meningkatkan kualitas pelayanan publik di Kementerian Agama Kabupaten Jombang - Wahyudi, Arif Nur (Maliki Interdisciplinary Journal, 2024)
In order to improve the quality of government service given to the public, needs to be created a one-door service program (ptsp ) that allows for simplification activities.The ministerial office of the community district is one of the government offices that has executed a united service system one door.This research was carried out to obtain data on the application of one-door united service as an effort to improve the quality of public service at the Ministry of Religion..This research uses a descriptive qualitative approach.Data obtained through observation results, interview, and documentation.The results obtained from the study that by implementing a unified service, one door of the community service process became effective and efficient